The Influence Of Interactivity And Ephemerality Of Instagram Advertisements In Shaping Perceived Value And Behavioral Intention - Amalia, Rika; Widodo, Teguh (eProceedings of Management, 2024)
Instagram stands out as a prominent platform, offering companies a valuable space to promote their offerings to a vast and diverse audience. To capture consumer interest, Instagram advertisements now incorporate innovative interactive features and ephemeral effects, enhancing their appeal and engagement. The objective of this study is to examine the influence of interactivity and ephemerality of instagram advertisements in shaping perceived value and behavioral intention. A quantitative research approach was employed in this study. Data from 239 participants were gathered through an online survey and analyzed utilizing SmartPLS 3.2.9 software employing Structural Equation Modeling. The findings indicate that the interactivity and ephemerality of Instagram Stories advertisements significantly influence three types of perceived value such as utilitarian, hedonic, and social value among female consumers of the fashion brand HeyLocal. Furthermore, these perceived values motivate positive behavioral intentions such as the intention towards social media activities, online search, and brand purchase. In contrast to social value, it was found that utilitarian and hedonic value do not directly impact brand purchase. In addition, our research revealed that consumers' purchase decisions can be reinforced through their engagement in social media activities and online information search. Keywords-interactivity, ephemerality, advertisement, Instagram, perceived value, behavioral intention